Nanogel-based drug delivery system as a treatment modality for diverse diseases: Are we there yet? - Brianna *,; Ayaz, Anwar *; Teow, Sin-Yeang; Wu, Yuan Seng * (Elsevier, 2024)
Traditional drug delivery systems (DDSs) are often associated with poor drug solubility, low bioavailability, and side effects, which severely limits the therapeutic potential of existing encapsulated drugs. A promising alternative to these conventional DDSs is a nanogel-based DDS. Possessing dual characteristics of both nanoparticles and hydrogels, nanogels have the capacity to transport and release drugs to the target site in a controlled manner while protecting encapsulated drugs from enzymatic degradation. With this, the therapeutic benefits of available drugs will be potentiated, and their side effects will be limited. Due to their tunability in size and chemical properties, nanogels can be functionalized to carry drugs of different properties. Given these merits, the potential of nanogel-based DDSs is currently being investigated as a treatment modality for various diseases. Among the diseases focused in this review are cancer, diabetes mellitus, neurodegenerative diseases, and ophthalmic conditions. To provide context, the synthesis and characterization of nanogels along with their delivery process to the target site is briefly reviewed. Besides, the challenges faced by researchers in translating nanogel-based treatments from preclinical to clinical practice are also discussed. The three identified challenges are (I) reproducibility and scalability; (II) enhanced site targeting, penetration and bioavailability; and (III) biocompatibility and safety of nanogels. Nonetheless, fueled by continuous development, nanogel-based drug carriers will be the future of drug delivery. To achieve this, future studies should focus on overcoming the aforementioned obstacles while providing evidence of safety to ensure the continued progress of ongoing developments towards clinical trials and ultimately, implementation for the benefit of patients.